BENTUK PENYAJIAN “MARHABAN” DI KAMPUNG CIWARU KELURAHAN CIPOCOK JAYA KECEMATAN CIPOCOK JAYA KOTA SERANG-BANTEN - Kharisma, Nur Hidayat; Suhaya, Suhaya; Permana, Rian (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2024)
oThis research focuses on how to serve Marhaban which is located in Ciwaru Village, Cipocok Jaya Village, Cipock Jaya District, Serang City, Banten. This research focuses on shaving events for babies who are usually only 7 days or 40 days old. This study has two problem formulations, one of which is related to the general description of Marhaban and the form of presentation of Marhaban art which is located in Kampung Ciwaru. This study uses qualitative methods to find answers to the problem formulation above. The researcher found that the Marhaban art is a hereditary art that is still practiced today in Ciwaru Village and is one of the arts that is cultivated. The sholawat marhaban program lasts approximately 20-30 minutes and consists of 4 to 10 people or more. When the sholawat marhaban is recited and begins to recite the sholawat marhaban, it is started by an imam or leader in the sholawat marhaban group according to the structure, poetry and style. The meaning of sholawat marhaban in each of the verses and verses already has meanings according to what is contained in the contents of the Qur'an or the hadith, as for the types of genres, namely the lagum bayati song with the meaning of the house because it is usually chanted as a foothold or for the following songs, the song lagum shoba has the meaning of the word longing because in the chant it is like a deep longing, the song lagum hijaz which in its meaning and the chant is very soft but impressive and lastly the song lagum rosta in the chant gives a feeling of sincerity and peace of mind.